2022
DOI: 10.1021/acsami.1c25203
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Spin State of Single Noble Metal Atoms by Hydroxyl for Selective Dehydrogenation of CH4 Direct Conversion to CH3OH

Abstract: The key scientific challenge for methane (CH 4 ) direct conversion to methanol (CH 3 OH) is considered to be the prevention of overoxidation of target products, which is restrained by the difficulty in the well-controlled process of selective dehydrogenation. Herein, we take single noble metal atomanchored hexagonal boron nitride nanosheets with B vacancies (M SA /B 1−x N) as the model materials and first propose that the dehydrogenation in the direct conversion of CH 4 to CH 3 OH is highly dependent on the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…As mentioned above, the dehydrogenation process on the BN surface is quite different from that on ZnO and P25, affecting the stabilization of CH 3 * and CH 3 O* intermediates, which are the important intermediates in the process of CH 3 OH generation [20] . Hence, a different dehydrogenation process might be the main factor affecting the product selectivity of CH 4 photooxidation into CH 3 OH over BN, ZnO, and P25 samples.…”
Section: Resultsmentioning
confidence: 98%
“…As mentioned above, the dehydrogenation process on the BN surface is quite different from that on ZnO and P25, affecting the stabilization of CH 3 * and CH 3 O* intermediates, which are the important intermediates in the process of CH 3 OH generation [20] . Hence, a different dehydrogenation process might be the main factor affecting the product selectivity of CH 4 photooxidation into CH 3 OH over BN, ZnO, and P25 samples.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have reported that the reaction process could take place on the in‐plane surface, armchair edge, or zigzag edge of BN nanosheets [17, 20, 27] . Hence, three types of calculated modes are constructed in Figure S24.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, the dehydrogenation process on the BN surface is quite different from that on ZnO and P25, affecting the stabilization of CH 3 * and CH 3 O* intermediates, which are the important intermediates in the process of CH 3 OH generation. [20] Hence, a different dehydrogenation process might be the main factor affecting the product selectivity of CH 4 photooxidation into CH 3 OH over BN, ZnO, and P25 samples. It is generally believed that during the photocatalysis process, the photoinduced carriers generated by semiconductors under light illumination may transfer to the surface to participate in the activation of the reactant and the further conversion process.…”
Section: Forschungsartikelmentioning
confidence: 99%
See 1 more Smart Citation
“…), atomic layer deposition method (ALD), 7,8 pyrolysis method, and mass-separation soft landing method. 9 Currently, various metal-based SACs have been successfully developed, incorporating metals such as platinum, 10 cobalt, 11 iron, 12 copper, 13,14 bismuth, 15 palladium, 16 ruthenium, 17 nickel, 10 and silver, 18 and their various applications are also introduced. For the characterization of SACs, it is tough to efficiently distinguish the existence of single metal atoms.…”
Section: Introductionmentioning
confidence: 99%